Graphene- and Graphene Oxide-Based Nanocomposite Platforms for Electrochemical Biosensing Applications - Thangamuthu, Madasamy (Int J Mol Sci, 2019)
Graphene and its derivatives such as graphene oxide (GO) and reduced GO (rGO) offer excellent electrical, mechanical and electrochemical properties. Further, due to the presence of high surface area, and a rich oxygen and defect framework, they are able to form nanocomposites with metal/semiconductor nanoparticles, metal oxides, quantum dots and polymers. Such nanocomposites are becoming increasingly useful as electrochemical biosensing platforms. In this review, we present a brief introduction on the aforementioned graphene derivatives, and discuss their synthetic strategies and structure–property relationships important for biosensing. We then highlight different nanocomposite platforms that have been developed for electrochemical biosensing, introducing enzymatic biosensors, followed by non-enzymatic biosensors and immunosensors. Additionally, we briefly discuss their role in the emerging field of biomedical cell capture. Finally, a brief outlook on these topics is presented.